A CASE OF HHV-6-ASSOCIATED ENCEPHALOMENINGITIS AGAINST THE GENERALIZED FORM OF ACUTE ENTERIC INFECTION - N.A. Myukke; T.B. Sentsova; V.K. Tatochenko; V.G. Bagayev ("Paediatrician" Publishers LLC, 2006)
(Voprosy sovremennoi pediatrii = Current pediatrics. 2006;5(5):104-105)